DETEKSI DINI RESIKO JATUH PADA LANSIA DI POSYANDU LANSIA KENTINGAN, KECAMATAN JEBRES, SURAKARTA - Erika Dewi Noorratri; Ari Septi Mei Leni; Ipa Sari Kardi (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Background :The falling risk is an event reported by a patient or family who sees an incident, which results in a person suddenly lying, sitting on the floor or lower place with or without loss of consciousness or injury. Falls can occurwhen the bodyâ€™s postural, control system fails to detectshifting and not repositioning the center of gravity toward the body support at the right time.Â  In Indonesia, the elderly who live in communities experience an annual fall or around 30%. The incidence of falls in the elderly living in the community increased from 25% at the age 70 to 35% after being over 75 years old. One cause of the fall is a disturbance in the pattern of roads. Therefore it is necessary to practice early detection of the risk of falling in the elderly. Target and output 100% of extension participants consisting of the elderly can increase their knowledge and understanding of early detection training on the risk of falling on the elderly. Methods of conducting lectures and demonstrations or exercises. The result of the elderly can mention how to detect risk in the elderly and can do exercises to prevent falls. Conclusion elderly know how to detect the risk of early fall in the elderly.Â